Controlling Lanthanide Exchange in Triple‐Stranded Helicates: A Way to Optimize Molecular Light‐Upconversion. Issue 46 (16th October 2017) - Zare, Davood; Suffren, Yan; Nozary, Homayoun; Hauser, Andreas; Piguet, Claude
Abstract: The kinetic lability of hexadentate gallium‐based tripods is sufficient to ensure thermodynamic self‐assembly of luminescent heterodimetallic [GaLn(L3 )3 ] 6+ helicates on the hour time scale, where Ln is a trivalent 4f‐block cation. The inertness is, however, large enough for preserving the triple‐helical structure when [GaLn(L3 )3 ] 6+ is exposed to lanthanide exchange. The connection of a second gallium‐based tripod further slows down the exchange processes to such an extent that spectroscopically active [CrErCr(L4 )3 ] 9+ can be diluted into closed‐shell [GaYGa(L4 )3 ] 9+ matrices without metal scrambling. This feature is exploited for pushing molecular‐based energy‐transfer upconversion (ETU) at room temperature. Abstract : Inert noncovalent [GaL 3 ] 3+ ions promote an unprecedented keystone mechanism for the capture/release of labile trivalent lanthanides on hour time scales. The cooperative operation of two [GaL 3 ] 3+ tripods pushes the limit of inertness to over months, which makes these new materials compatible with the preparation of solid‐state solutions displaying molecular‐based energy‐transfer upconversion at room temperature.